PENGGUNAAN WASEI-EIGO DALAM BUKU BAHASA JEPANG UNTUK PEMBELAJAR ASING TINGKAT MENENGAH/CHUUKYUU - Hidayat, Ari Teguh; Rahayu, Nana; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study discusses the use wasei-eigo contained in the book Japanese language intermediate level for foreign learners/chuukyuu. The purpose of this study was to determine the difference between gairaigo and wasei-eigo and how to classify wasei-eigo according Shibasaki Tamaoka and Takatori Yuki. This study used qualitative descriptive method. The object of research is the following text books Minna no Nihongo Chuukyuu I and Dekiru Nihongo. From the result of research, author found there are four kinds of wasei-eigo, they are wasei-eigo wich changing the meaning, wasei-eigo which shortening of the word, wasei-eigo which combination of some of the morpheme and wasei-eigo not originating from the English original. In this study there is also a wasei-eigo which changes the meaning as well as shortening the word. The use wasei-eigo most commonly found in the book Japanese language intermediate level for foreign learners/chuukyuu are wasei-eigo which changing the meaning and wasei-eigo which shortening the word. This is because when a foreign language is adapted in Japan, it does not just change the pronunciation, but the word itself could change in meaning and in function.Key Word: Gairaigo, Wasei-eigo, Chuukyuu, Intermediate